S144 Mixed ventilatory defects in pulmonary sarcoidosis: prevalence and clinical features. (December 2018) - Kouranos, V; Ward, S; Kokosi, M; Castillo, D; Chua, F; Judge, E; Thomas, S; Van Tonder, FV; Devaraj, A; Nicholson, A; Maher, T; Renzoni, E; et al.
Abstract : Introduction and Objectives: Mixed disease is largely understudied in pulmonary sarcoidosis as static lung volumes are seldom taken into account in historical series. Moreover, increases of static lung volumes expected in an obstructive process are not considered in the current ATS/ERS definition of mixed disease. The aim of our study was to assess the prevalence of mixed disease in pulmonary sarcoidosis and its clinical associations. Methods: Patients with pulmonary sarcoidosis (n=1110) were evaluated. The range of static volumes expected in association with a pure obstructive process was quantified in a control cohort of COPD patients (n=899). Mixeddefects were defined using: a) ATS/ERS criteria; and b) modified criteria based on expected TLC values, defined against FEV1/FVC levels in COPD control subjects. Measurements and main results: A mixed ventilatory defect was present in 115 (10.4%) sarcoidosis patients, increasing to 12.4% with the use of modified criteria. Mixed disease, defined using ATS/ERS criteria, was associated with lower DLco levels (50.7±16.3 vs 70.8±18.1, p<0.0001), a higher prevalence of chest radiographic stage IV disease (63.5% vs 38.3%, p<0.0001), and higher mortality (HR 2.36, 95% CI: 1.34 to 4.15, p=0.003) than in patients with an isolated obstructive defect. These findings were unchanged when mixed disease was defined using modified ATS/ERS criteria. Conclusions: Mixed disease is present in 25%–35% of patients with pulmonary sarcoidosis patients with airflow obstruction and is associated with lower DLco levels, a higher prevalence of chest radiographic stage IV disease and higher mortality than in patients with an isolated obstructive defect.